Studi e ricerche di sanità pubblica e delle professioni sanitarie Studies and Researches in Public Health and Health Professions - Maria Triassi (FedOA - Federico II University Press, 2019)
This book belongs to a new collection promoted by the School of Medicine at Federico II University of Naples. The publication wants to encourage communication between those who are engaged in Research, Prevention, and the application of Medicine in various medical specialties. Spreading the culture of prevention is of primary importance in planning health policies. Research topics will be: Health education and promotion, Infectious diseases, Sports medicine, Cancer prevention, Health prevention, Psychiatry and pathological addiction, Health and environment, Animal health, Public health , Food Safety, Vaccinations.